Protective effect of hexahydrobenzo[c]phenanthridine alkaloids isolated from Corydalis ambigua var. amurensis on myocardial ischemia-hypoxia cells. (September 2016) - Liu, Zhi-Hui; Li, Qiao; Chang, Sheng; Yang, Zhi-You; Han, Na; Yin, Jun
Graphical abstract: Highlights: Hexahydrobenzo[c] phenanthridine alkaloids were isolated from the leaves of Corydalis ambigua var. amurensis . Two new and six known hexahydrobenzo[c] phenanthridine-type alkaloids were isolated. All the compounds except comp.6 showed the remarkable protective effect on myocardial ischemia-hypoxia cells. Abstract: Two new hexahydrobenzo[c] phenanthridine alkaloids, ambiguanine H (1 ) and ambiguanine I (2 ) together with six known hexahydrobenzo[c] phenanthridine alkaloids (3 –8 ), were isolated and purified from the Corydais ambigua var. amurensis leaves. Their structures were elucidated by extensive spectroscopic methods and all the compounds except comp.6 showed the remarkable protective effect on myocardium ischemia-hypoxia cells and comp.4 was the most active compound with cell viability of 49.4, 53.3, 68.2 and 84.5% in the range of at 0.01–10 μmol/L which were stronger than that of salvia acid B.